Mott Transitions in the 2-band Hubbard Model: A Coherent Potential Approximation Study - Anh, Le Duc; Tuan, Hoang Anh (Communications in Physics, 2012)
The half-filled isotropic degenerate two-band Hubbard model is studied within coherent potential approximation. The model is characterized by an Ising-type Hund’s exchange coupling, intra- and inter-orbital Coulomb parameters. We found that the band degeneracy slightly reduces the Mott-Hubbard critical value \(U_C\). We reveal that the system can have two distinct critical values for Mott-Hubbard transitions.